2018
DOI: 10.3390/ijerph15020207
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution, Chemical Fraction and Fuzzy Comprehensive Risk Assessment of Heavy Metals in Surface Sediments from the Honghu Lake, China

Abstract: Spatial concentrations and chemical fractions of heavy metals (Cr, Cu, Pb, Zn and Cd) in 16 sampling sites from the Honghu Lake were investigated using an atomic absorption spectrophotometer and optimized BCR (the European Community Bureau of Reference) three-stage extraction procedure. Compared with the corresponding probable effect levels (PELs), adverse biological effects of the studied five sediment metals decreased in the sequence of Cr > Cu > Zn > Pb > Cd. Geo-accumulation index (Igeo) values for Cr, Cu,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Interestingly, we found that As and Cr were found to have the highest health risk among the selected trace elements in the surface water from Honghu Lake, as in E . crassipes 36,52 , while the opposite was observed in the sediment 37,49 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly, we found that As and Cr were found to have the highest health risk among the selected trace elements in the surface water from Honghu Lake, as in E . crassipes 36,52 , while the opposite was observed in the sediment 37,49 .…”
Section: Discussionmentioning
confidence: 89%
“…The detailed results are shown in Table S1. The data of the trace elements in the sediment are derived from a previous study 49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling fish farms are sporadically distributed around Honghu Lake, and the specific location of each fish farm is marked in Figure S1 . The water temperature in Honghu Lake ranges from 27 °C–29 °C, and the mean pH value is 7.59 [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The contour map of spatial distribution of heavy metal elements can reveal the distribution characteristics, spatial migration and sources of heavy metals to a certain extent [18,19]. The contour map of spatial distribution of heavy metals in the study area was plotted by Surfer software (Figure 3), and the Kriging interpolation method was used to calculate the unmeasured area.…”
Section: Distribution Of Heavy Metalsmentioning
confidence: 99%